Enzyme-linked immunosorbent assay to diagnose human leptospirosis: a meta-analysis of the published literature - Signorini Porchietto, Marcelo Lisandro (2013)
We report an evaluation of the accuracy of ELISA for the detection of Leptospira-specific antibodies in humans. Eighty-eight studies published in 35 articles met all inclusion criteria and were submitted to meta-analysis. Pooled sensitivity and specificity were 0·779 (95% CI 0·770-0·789) and 0·913 (95% CI 0·908-0·917), respectively, and the area under the curve was 0·964. Heterogeneity across studies was statistically significant, but none of the sources of heterogeneity (disease stage, antigen used, antibody detected) could fully explain this finding. Although the convalescent stage of disease was significantly associated with higher diagnostic accuracy, IgM ELISA was the best choice, regardless of the stage of disease. Negative ELISAs (IgG or IgM) applied in the acute phase do not rule out leptospirosis due to the possibility of false-negative results. In this case it is advisable to request a second blood sample or to apply a direct method for leptospiral DNA.